2023
DOI: 10.3390/molecules28031244
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Co-Crystallization of Kojic Acid with Silver(I), Copper(II), Zinc(II), and Gallium(III) for Potential Antibacterial Applications

Abstract: Co-crystallization of kojic acid (HKA) with silver(I), copper(II), zinc(II), or gallium(III) salts yielded three 1D coordination polymers and one 0D complex in which kojic acid was present as a neutral or anionic terminal or bridging ligand. All reactions were conducted mechanochemically via ball milling and manual grinding, or via slurry. All solids were fully characterized via single-crystal and/or powder X-ray diffraction. As kojic acid is a mild antimicrobial compound that is widely used in cosmetics, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…For example, some of us have reported that the antibiotic activity of the well-known antibiotic ciprofloxacin can be strengthened via cocrystallization with the natural products carvacrol and thymol . Analogously, we have shown that the antimicrobial compound proflavine, and recently also kojic acid, can be cocrystallized with metal salts of silver, zinc, and gallium to increase the minimal inhibition concentration of the drug activity toward bacteria. The preparation of cocrystals of known drugs, as well as the quest for new combinations of natural antibacterials, have been shown to be successful in the development of improved or novel drugs; extensive work of other research groups is well documented in a recent review by Nangia …”
Section: Discussionmentioning
confidence: 99%
“…For example, some of us have reported that the antibiotic activity of the well-known antibiotic ciprofloxacin can be strengthened via cocrystallization with the natural products carvacrol and thymol . Analogously, we have shown that the antimicrobial compound proflavine, and recently also kojic acid, can be cocrystallized with metal salts of silver, zinc, and gallium to increase the minimal inhibition concentration of the drug activity toward bacteria. The preparation of cocrystals of known drugs, as well as the quest for new combinations of natural antibacterials, have been shown to be successful in the development of improved or novel drugs; extensive work of other research groups is well documented in a recent review by Nangia …”
Section: Discussionmentioning
confidence: 99%
“…For example, a study found that kojic acid and tea polyphenols had a strong synergistic antibacterial effect against spoilage bacteria in refrigerated sea bass fillets [20]. Another study investigated the potential antibacterial properties of kojic acid in conjunction with metal cations by cocrystallizing them and reported that co-crystallization of kojic acid with silver(I), copper (II), zinc (II), and gallium (III) demonstrated increased antibacterial activity [21]. Furthermore, kojic acid-grafted konjac glucomannan oligosaccharides were reported to have high antimicrobial effects against bacteria like S. aureus in a study [22].…”
Section: Synergistic Antibacterial Activitymentioning
confidence: 99%
“…Previous studies have shown that the response of gram‐positive Staphylococcus aureus appears to be different, with an observed minimum inhibitory concentration (MIC) of 1.5 mg/mL and minimum biocidal concentration (MBC) values exceeding 6.25 mg/mL [5]. This suggests that achieving a bactericidal effect against S. aureus within the tested concentration range may be limited.…”
Section: Introductionmentioning
confidence: 99%